IMPLEMENTASI LITERASI DIGITAL DALAM PEMBELAJARAN PENDIDIKAN PANCASILA KELAS V SEKOLAH DASAR - Haifa Anjani, Karin; Anggraeni Siwi , Dwi (STKIP Subang, 2026)
This study aims to describe the implementation of digital literacy in Pancasila Education learning for fifth grade elementary school students and identify the obstacles faced in implementing digital literacy during Pancasila Education learning for fifth grade elementary school students. This study uses a qualitative research method with a descriptive qualitative research type. Data collection techniques were carried out using observation, interviews, and documentation. The data analysis technique for this study used interactive data analysis techniques. The results of the study indicate that the implementation of digital literacy in Pancasila Education learning on the topic